Omonimia, polisemia, ambiguità e altre questioni semantiche (Atti del Sodalizio Glottologico Milanese, 2019)
Homonymy, Polysemy, Ambiguity and other Semantic Issues. Meaning (literal and non-literal) may be regarded as a a many-faceted, multi-layered dynamic concept encompassing a number of different core and outer dimensions. Within such an approach, the very fact that polysemes, homonyms, homophones and homographs exist is a test bench for probing and working out a semantic theory, since they are not mereaccidents, but linguistic resources for creative and artistic purposes. Ambiguity and multiplicity of meaning contribute to making language the powerful and versatile tool it is. The languages considered here are Japanese, Chinese, Sanskrit, Prakrits, Brajbhāṣā, Hmong, Zhuang, Toda and Tamil, together with their literatures, cultures and traditions. Special emphasis is laid upon śleṣa, kakekotoba and other instances of creative uses of polysemy, homonymy and ambiguity. KEYWORDS: Homonyms, homophones, homographs, ambiguity, polysemy